Effect of Bifidobacterium longum subsp. longum on the proliferative and tight-junction activities of Human Fetal Colon Epithelial Cells. (November 2021) - Guan, Jiaqi; Liu, Fei; Zhao, Sijia; Evivie, Smith Etareri; Shi, Jialu; Li, Na; Zhao, Li; Yue, Yingxue; Xie, Qinggang; Huo, Guicheng; Li, Bailiang
Graphical abstract: Highlights: Bifidobacterium longum enhanced cell proliferation, prevented apoptosis, regulated cycle. Bifidobacterium longum promoted energy and protein metabolism of CCD841 CoN cells. Bifidobacterium longum activated Wnt/β-Catenin and PI3K/Akt/mTOR signaling pathway. Bifidobacterium longum up-regulated protein expression levels of cells' tight junction. Abstract: Bifidobacterium species are the dominant bacteria in the intestinal tract of infants and young children, and are closely related to intestinal development. The Bifidobacterium longum subsp. longum strains K2-21-4 has been shown to promote the proliferation of CCD841 CoN cells. We evaluate the effect of B. longum on the proliferation of CCD841 CoN cells and tight junction using a lipopolysaccharide (LPS)-induced injury model. We discovered that B. longum K2-21-4 increased the cell proliferation rate and total cell protein content, shortened the cell cycle process, reduced apoptosis, and increased the activity of adenosine triphosphate (ATP)ases, aspartate aminotransferase, and alanine aminotransferase. Real-time reverse transcription quantitative polymerase chain reaction and western blotting showed that B. longum K2-21-4 activated Wnt/β-Catenin and PI3K/Akt/mTOR signaling pathway at gene transcription and protein expression levels up-regulated the expression level of protein related to the tight junction. Our findings suggest that B. longum K2-21-4 could regulate intestinal development by promoting cell proliferation and accelerating the maturation of the internal barrier.